Behaviours of wall and soil during pre-excavation dewatering under different foundation pit widths. (November 2019) - Zeng, Chao-Feng; Zheng, Gang; Zhou, Xiao-Feng; Xue, Xiu-Li; Zhou, Hai-Zuo
Abstract: Dewatering before excavation can induce obvious wall deflection; however, engineers rarely monitor it before excavation. This traditional monitoring data will undervalue the environmental effect induced by foundation pit construction. In this study, a dewatering test conducted in a large-scale foundation pit is reported. Then, 35 numerical models considering different pit widths are developed to simulate the dewatering process based on the test results. The pit deformation behaviours during dewatering with different pit widths ( W p ) are analysed. The results indicate that time effect and size effect are two features of dewatering-induced deformation: (1) the pit deformations grow rapidly during the first few days of dewatering, but the growth rate decreases continuously; (2) the wider pit exhibits greater deformations, but there exists a critical pit width (approximately 40 m in this study), within which the pit deformations grow rapidly (average approximately 0.03% of W p increase); however, with W p being greater than the critical width, the pit behaviours demonstrate a slight difference.